CHANGE OF LOCAL MYOCARDIAL CONTRACTILITY DUE TO SELECTION OF DIFFERENT ARRHYTHMIA TREATMENT STRATEGIES IN PATIENTS WITH ISCHEMIC HEART DISEASE AND PAROXYSMAL ATRIAL FIBRILLATION - V. I. Podzolkov; A. I. Tarzimanova (Рациональная фармакотерапия в кардиологии)
Aim. To study the change of local myocardial contractility in patients with ischemic heart disease (IHD) and paroxysmal atrial fibrillation (AF) during treatment with amiodarone 200 mg daily compared with bisoprolol therapy 5 mg daily.Material and methods. A total of 47 IHD patients with persistent AF were enrolled in the study. Sinus rhythm (SR) was restored during the first 24 hours after admission in all the patients. After SR restoration patients were randomly allocated into two groups receiving either amiodarone 200 mg/day during 6 months for SR maintenance (group 1) or bisoprolol 5 mg daily for ventricular rate (VR) control (group 2). To estimate a local myocardial systolic function all the patients were undergone steady-state radionuclide ventriculography in the first 24 hours after SR restoration and 6 months later.Results. Sinus rhythm saving at amiodarone therapy within 6 months led to an improvement of the local myocardial contractility of the left ventricle with a significant increase in normokinesis zones from 79 (58.1%)  to 92 (67.6%), hypokinesis and akinesia zones reduction from 46 (33.8%)  to 41 (30.2%)  and from 11 (8.1%) to 3 (2.2%) (p<0.05), respectively. Achieving the target values of ventricular rate during the remaining episodes of AF in patients of group II did not significantly affect the local left ventricle contractility.Conclusion. 6-month SR maintenance with amiodarone intake in IHD patients with persistent AF resulted in significant reduction of akinesia zones and increase in the number of normokinesia segments.